KAJIAN NUMERIK BACK FLOW CAMPURAN BATUBARA–AIR PERPIPAAN BA-300 PADA PYRITES HOPPER SYSTEM DI PLTU UNIT 8 PT. POMI PAITON - Khairuddin Khairuddin; Priyonggo SL Projek; Moballa Burniadi (Proceedings Conference on Marine Engineering and its Application, 2018)
Pulverizer is one of the most important equipment in PLITU PAITON Unit 8, the pulverizer has supporting equipment, one of which is the pyrites hopper system. The functions pyrites hopper is to accommodate coal reject from pulverizer which will be directed towards SSCC using a jet pump. The occurrence of backflow causes damage to the pulverizer on the floor plate. Thermal stress occurs because the backflow of the BA-300 piping flow that enters the pulverizer floor plate temperature drops. This research discusses the backflow causes that occur in the BA-300 pipeline and alternative solutions. This research phase starts from the identification of backflow problems, data collection and literature study regarding backflow on the swing check valve, as well as CFD (Comptational Fluid Dynamics), modeling of existing BA-300 piping system, search and evaluation of alternative solutions. From the simulation results, the coal particles are sandwiched between the disc and casing check valve because the coal particles settle at the bottom of the check valve, which is caused by the amount of flow rate of coal 2.6 kg / s. Of the 6 variations made, the reduction in flow rate with the amount of 1.7 kg / s was not found again pinched coal even though there was still a bit of coal sequestration.Keyword : Backflow, CFD, Swing check valve model.